(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ichthyosis are a heterogeneous group of Hereditary and acquired disorders of keratinization characterized by the presence of visible scales on skin surface. The word is derived from Greek root for fish – icthys. There are two major types of ichthyosis that is Congenital and Acquired. Ichthyosis vulgaris one among congenital ichthyosis is the most common with an estimated incidence rate of 1 in 250 births, with an onset in early childhood characterized by fine, whitish scales which often sheds off. The severity of symptoms can vary enormously from mildest, most common types such as Ichthyosis vulgaris, up to life threatening condition such as Harlequin Ichthyosis. In general all types of Ichthyosis has been identified as rare disease by National Organization for Rare Disorders (NORD). There is currently no cure for ichthyosis only symptomatic management is done. Topical application is the major treatment according to modern medicine, which should be used daily In Ayurveda skin diseases have been described under the heading Kushta; which is again classified into Mahakushta and Kshudrakushta. Ekakushta, one among Kshudrakushta having Dosa predominance of Vata Kapha shares features more or less similar to ichthyosis vulgaris. Ayurvedic management aims at clearing the Srotas and providing internal and external Snehana has produced a markable change in a case of congenital ichthyosis.